Children Crimes and Media - Tokdemir, Mehmet; Küçüker, Hüdaverdi (The Bulletin of Legal Medicine, 2000)
In this study, 106 male children/adolescents (aged between 12-17 years, mean: 1S.0± 1.2) who have been sent to the correctional institutes for children at Elazığ were compared with 126 male students (aged betweenl3-18 years, mean: 13.0+1,3) with similar socio-economic levels who didn’t commit a crime before, for their media and music preferences and to search for the difference of attitudes towards media between two groups were aimed. Before they were sent to the correctional institute at Elazığ, these children/adolescents watched TA’ for 34-39 hours/week while the control subjects have watched TV for 19-26 hours/week. While 51.9% of the convicted children/adolescents preferred movies of war and adventure containing violence, the ratio for the control group was 25.4%. The significant difference between the two groups showed the role of media on violent behavior. As a conclusion its necessary that the involved authorities should take serious precautions on this issue. Keywords: Children/adolescent delinquency, violence in media, music and violence.